RESPON PETANI ATAS KEMISKINAN STRUKTURAL (Kasus Desa Perkebunan dan Desa Hutan) - Heru Purwandari (University of Jember, 2011)
Governmental development paradigm during the time in bearing with experienced resources management had marginalized and impoverished certain groups in the society. This condition make a structural poverty which emergence from inequality resources access between elite and peasant. Inequality cause the marjinalization of the society, and its implication to the empowerment of the society itself. Respon of the structural poverty has shown through two community are forest village and plantation village. That communities have different characteristic and the implications different too. But, the goal of respons have a same is out from structural condition. Key Words: structural poverty, inequality access resources, respons of structural poverty